RAILWAY INFRASTRUCTURE CAPACITY MANAGEMENT FOR AD-HOC TRAINS ON THE SŽDC NETWORK - Petr Nachtigall; Martin Škárek (Acta Polytechnica CTU Proceedings, 2016)
The paper describes basic principles of ad-hoc routes assignment. Each carrier has its own interface called information system KADR with SŽDC for capacity requests management. The paper describes all steps which must be done before train departure.